2022
DOI: 10.1111/ced.15058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors associated with sexual dysfunction in psoriasis in a cohort of 1409 patients

Abstract: MCS has a large impact on patients' mental wellbeing and their ability to carry out activities of daily living, because of the 'hidden dangers' of environmental chemical exposure. This impact is further heightened by patients feeling that their condition is not recognized by others, leading to a 'profound sense of invisibility'. 2 The prevalence of physician-diagnosed MCS has been found to be 0.5%. 3 No objective proof of a causal relationship between chemical exposure and symptoms has been shown, and the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, our study showed more abnormalities in subjects undergoing systemic treatment, it should be emphasized that the topical therapy can also be troublesome due to the consistency and fragrance of the topical agents ( 19 ). We must also highlight that, unfortunately, we were not able to assess the severity or resolution of lesions after the treatment.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, our study showed more abnormalities in subjects undergoing systemic treatment, it should be emphasized that the topical therapy can also be troublesome due to the consistency and fragrance of the topical agents ( 19 ). We must also highlight that, unfortunately, we were not able to assess the severity or resolution of lesions after the treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Topical and systemic antipsoriatic treatment is considered to be another cause of sexual dysfunctions ( 12 , 19 ). For example, methotrexate can lead to erectile dysfunction and reduced libido ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation